Whole-body magnetic resonance imaging in pediatric oncology - recommendations by the Oncology Task Force of the ESPR - Schäfer, Jürgen F; Granata, Claudio; von Kalle, Thekla; Kyncl, Martin; Littooij, Annemieke S; Di Paolo, Pier Luigi; Sefic Pasic, Irmina; Nievelstein, Rutger A J; Oncology Task Force of the ESPR (Pediatric radiology, 2020)
The purpose of this recommendation of the Oncology Task Force of the European Society of Paediatric Radiology (ESPR) is to indicate reasonable applications of whole-body MRI in children with cancer and to address useful protocols to optimize workflow and diagnostic performance. Whole-body MRI as a radiation-free modality has been increasingly performed over the last two decades, and newer applications, as in screening of children with germ-line mutation cancer-related gene defects, are now widely accepted. We aim to provide a comprehensive outline of the diagnostic value for use in daily practice. Based on the results of our task force session in 2018 and the revision in 2019 during the ESPR meeting, we summarized our group's experiences in whole-body MRI. The lack of large evidence by clinical studies is challenging when focusing on a balanced view regarding the impact of whole-body MRI in pediatric oncology. Therefore, the final version of this recommendation was supported by the members of Oncology Task Force.
Keywords: Magnetic Resonance Imaging; magnetická rezonanční tomografie; Consensus; Humans; Cancer predisposition syndromes; poradní výbory; dítě; Child; Neoplasia; Surveillance; Advisory Committees; Whole-body imaging; lidé; Europe; Children; Staging; konsensus; celotělové zobrazování; Magnetic resonance imaging; Neoplasms; nádory; Whole Body Imaging; Evropa